THE SPECIFIC FEATURES OF SPEECH THERAPY GAMES IN SPEECH DISORDERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article systematically covers the specific features of speech therapy games in speech disorders. The article describes in detail the games organized for children with speech disorders during speech therapy sessions, the theory of special education, creative games and games with rules.